2001
DOI: 10.1021/ja016451g
|View full text |Cite
|
Sign up to set email alerts
|

C−H Bond Activation by a Ferric Methoxide Complex:  Modeling the Rate-Determining Step in the Mechanism of Lipoxygenase

Abstract: Lipoxygenases are mononuclear non-heme iron enzymes that regio- and stereospecifcally convert 1,4-pentadiene subunit-containing fatty acids into alkyl peroxides. The rate-determining step is generally accepted to be hydrogen atom abstraction from the pentadiene subunit of the substrate by an active ferric hydroxide species to give a ferrous water species and an organic radical. Reported here are the synthesis and characterization of a ferric model complex, [Fe(III)(PY5)(OMe)](OTf)(2), that reacts with organic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
248
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(271 citation statements)
references
References 96 publications
22
248
1
Order By: Relevance
“…8-10). In all three cases, DHA was oxidized and kinetic isotope effects (KIEs) Ͼ 9 were observed with DHA-d 4 as substrate ( Table 2), indicating that hydrogen atom abstraction is the rate-determining step for the oxidations (32,33). Analysis of the oxidation products showed that anthracene was produced in Ϸ50% yield for 1b and 4b, as deduced from its characteristic UV bands (SI Figs.…”
Section: X-ray Absorption Spectroscopy (Xas)mentioning
confidence: 91%
“…8-10). In all three cases, DHA was oxidized and kinetic isotope effects (KIEs) Ͼ 9 were observed with DHA-d 4 as substrate ( Table 2), indicating that hydrogen atom abstraction is the rate-determining step for the oxidations (32,33). Analysis of the oxidation products showed that anthracene was produced in Ϸ50% yield for 1b and 4b, as deduced from its characteristic UV bands (SI Figs.…”
Section: X-ray Absorption Spectroscopy (Xas)mentioning
confidence: 91%
“…The last stage of the TA biosynthesis pathway is the non-enzymatic oxidation of traumatin into traumatic acid. TA synthesis is induced and regulated mainly by environmental stress factors, especially wounding, but also by high and low temperatures, UV, or osmotic shock (Zimmerman and Coudron 1979, Siedow 1991, Stelt et al 2000, Goldsmith et al 2002, Howe and Schilmiller 2002.…”
Section: Introductionmentioning
confidence: 99%
“…Although tantalizing, the relatively small difference in the observed KIEs is not sufficient to conclude that there is a greater tunneling contribution in the enzymatic process than that of the uncatalyzed reaction in water. A number of experimental and theoretical studies suggested that the extent of tunneling was the same in several enzymes as in model reactions in solution (2,9,10), whereas other experiments showing differential tunneling behaviors may be attributed to different reaction mechanisms (2,(11)(12)(13). Nuclear tunneling cannot be measured directly, and the best experimental diagnostic of tunneling is through measurement of kinetic isotope effects (14).…”
mentioning
confidence: 99%